Adsorption of cadmium (II) ions from aqueous solution using palm oil fly ash (POFA) - Abdul Aziz, Abdul Shukor; Abd Manaf, Latifah; Che Man, Hasfalina; Hamdan, Mas Ernawati (Faculty of Engineering, Universiti Putra Malaysia, 2012)
The aim of this study is to conduct comprehensive studies of Cd (II) ions removal using a low-cost locally available adsorbent which is from agricultural waste. Batch adsorption experiments were conducted for the adsorption of Cd (II) ions from aqueous solution using palm oil fly ash (POFA). The parameters studied include contact time, pH, adsorbent dosage and adsorbate initial concentration. The results showed that the adsorption of Cd (II) ions was very fast initially and equilibration time was achieved after 210 min of contact time. The optimum pH was obtained at pH 9.0. High pH (≥ 9.0) favours the adsorption and removal of Cd (II) ions from aqueous solution. As the adsorbent dosage increased, the removal of Cd increased, whereas the adsorption capacity decreased. Higher initial concentration led to lower removal percentages but higher adsorption capacity. The adsorption behavior of Cd (II) ions fitted Langmuir and Freundlich isotherms well, but followed Langmuir isotherm more precisely, with a maximum adsorption capacity and R2 value of 15.823 mg/g and 1.0 respectively. The applicability of Langmuir isotherm suggested the formation of monolayer coverage of Cd (II) ions at the outer surface of the adsorbent. Therefore, this study demonstrated that POFA could be used successfully for adsorption of Cd (II) ions from aqueous solution.